THE THE ANALYSIS OF ‘TONE’ IN THE MONKEY’S PAW BY W.W.JACOBS - Indrawan, Zunus (JURNAL LITERARY CRITICISM, 2019)
This study aims to understand the Tone of the story of The Monkey's Paw By W.W. Jacobs Knowledge of the fic element Tone which aims to increase appreciation reader. This research is qualitative research with textual methods. Textual methods will investigate and analyze literary works with an emphasis on content analysis. According to Guba and Lincoln (in Moleong, 2005: 220), content analysis is done by interpreting and making conclusions through the identification of specific themes in the text objectively and systematically. Therefore, The Monkey's Paw By W.W.'s short story Jacobs serves to show that everything that will be done must be full of consideration and think of the consequences that will occur. This paper analyzes the short of The Monkey's Paw, one of the famous short stories by W.W. Jacobs. The results of this study reveal that W.W. Jacobs has shown what will happen from actions that ignore his words, especially about the consequences. The author hopes that this paper can be useful for readers in develop knowledge about plans as one element of fiction and can help readers to understand the tone of the story of the story of The Monkey's Paw By W.W. Jacobs.   Keywords: Tone, qualitative research, quotations, the story of The Monkey's Paw By W.W. Jacobs.